Deforestation impacts on soil organic carbon stocks in the Semiarid Chaco Region, Argentina - Villarino, Sebastián Horacio (2017)
Land use change affects soil organic carbon (SOC) and generates CO2 emissions. Moreover, SOC depletion entails degradation of soil functions that support ecosystem services. Large areas covered by dry forests have been cleared in the Semiarid Chaco region of Argentina for cropping expansion. However, deforestation impacts on the SOC stock and its distribution in the soil profile have been scarcely reported. We assessed these impacts based on the analysis of field data along a time-since-deforestation-for-cropping chronosequence, and remote sensing indices. Soil organic C was determined up to 100 cm depth and physically fractionated into mineral associated organic carbon (MAOC) and particulate organic C (POC). Models describing vertical distribution of SOC were fitted. Total SOC, POC and MAOC stocks decreased markedly with increasing cropping age. Particulate organic C was the most sensitive fraction to cultivation. After 10 yr of cropping SOC loss was around 30 %, with greater POC loss (near 60 %) and smaller MAOC loss (near 15 %), at 0-30 cm depth. Similar relative SOC losses were observed in deeper soil layers (30-60 and 60-100 cm). Deforestation and subsequent cropping also modified SOC vertical distribution. Soil organic C loss was negatively associated with the proportion of maize in the rotation and total crop biomass inputs, but positively associated with the proportion of soybean in the rotation. Without effective land use polices, deforestation and agricultural expansion can lead to rapid soil degradation and reductions in the provision of important ecosystem services.